2013
DOI: 10.1111/jhn.12088
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and obesity: influence in mortality and readmissions in chronic obstructive pulmonary disease patients

Abstract: Obesity in patients hospitalised for COPD substantially reduces in-hospital mortality risk and the possibility of early re-admittance. Malnutrition is associated with an important increase in in-hospital mortality and risk of re-admittance in the 30 days following discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 36 publications
(60 reference statements)
2
44
1
Order By: Relevance
“…A similar role has been found in patients suffering from malnutrition (OR, 1.29; 95% CI, 1.21-1.37) 24 and in patients with reduced levels of proteinemia (OR, 2.01; 95% CI, 1.03-3.94), 31 increased levels of partial arterial carbon dioxide pressure (PCO 2 ) (OR, 1.02; 95% CI, 1.00-1.05), 31 or C-reactive protein (Z7.6 mg/L; OR, 7.41; 95% CI, 1.34-40.91), 30 all measured in the predischarge or the discharge phase. Surprisingly, in a retrospective study of a very large cohort of COPD patients, 24 obesity played a protective role (OR, 0.87; 95% CI, 0.84-0.91) in readmission due to all causes.…”
Section: What Factors Can Predict a Readmission In 30 Days Or Less?supporting
confidence: 69%
See 3 more Smart Citations
“…A similar role has been found in patients suffering from malnutrition (OR, 1.29; 95% CI, 1.21-1.37) 24 and in patients with reduced levels of proteinemia (OR, 2.01; 95% CI, 1.03-3.94), 31 increased levels of partial arterial carbon dioxide pressure (PCO 2 ) (OR, 1.02; 95% CI, 1.00-1.05), 31 or C-reactive protein (Z7.6 mg/L; OR, 7.41; 95% CI, 1.34-40.91), 30 all measured in the predischarge or the discharge phase. Surprisingly, in a retrospective study of a very large cohort of COPD patients, 24 obesity played a protective role (OR, 0.87; 95% CI, 0.84-0.91) in readmission due to all causes.…”
Section: What Factors Can Predict a Readmission In 30 Days Or Less?supporting
confidence: 69%
“…Sex was also identified in 3 of these studies, [24][25][26] although with contrasting results. A Chinese 25 retrospective study evaluating all readmissions to the hospital in COPD patients found that male sex was associated with an increased risk of readmission (OR, 1.45; 95% CI, 1.38-1.52); a protective role in comparison with the other sex was tested in 2 retrospective studies 24,26 for all readmitted COPD patients, showing a reduced risk of readmission in men 24 (OR, 0.75; 95% CI, 0.72-0.77) and women 26 (OR, 0.9; 95% CI, 0.7-0.9).…”
Section: What Factors Can Predict a Readmission In 30 Days Or Less?mentioning
confidence: 80%
See 2 more Smart Citations
“…Malnutrition is correlated with increased risk of 30-day readmission rate, even when controlling for confounders. Interestingly, obesity affords a modest protective impact on readmission [30]. Poor adherence to treatment and followup has recently been implicated as an independent predictor of increased readmission rate [29].…”
Section: Patient Risk Factorsmentioning
confidence: 99%